(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
The success of treatment of acute ischemic stroke depends essentially on the time passed until the vessel is reopened. For this reason, training is necessary for the already complicated endovascular stroke treatment under high time pressure. Current in-vitro models do not offer the full range of different stroke cases and the use of various treatment options. This paper describes a conceptual design of a stroke in-vitro model using additive manufacturing to map a range of patient-based training cases. The model considers special aspects of vessels of elderly patients, such as curvatures and stenoses, which complicate the removal of clots.